2015
DOI: 10.1093/ndt/gfv293
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of iron isomaltoside 1000 versus oral iron in non-dialysis-dependent chronic kidney disease patients with anaemia

Abstract: BackgroundIron deficiency anaemia is common in patients with non-dialysis-dependent chronic kidney disease (NDD-CKD) and is often treated with oral or intravenous (IV) iron therapy. This trial compared the efficacy and safety of IV iron isomaltoside 1000 (Monofer®) and oral iron in NDD-CKD patients with renal-related anaemia.MethodsThe trial was a Phase III open-label, comparative, multicentre, non-inferiority trial conducted in 351 iron-deficient NDD-CKD patients, randomized 2:1 to either iron isomaltoside 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 12 publications
6
63
2
5
Order By: Relevance
“…Studies comparing oral to IV iron in this population have generally found greater efficacy for IV iron. 17,18 However, to truly understand oral iron efficacy, it would require parallel group testing against placebo or, to a lesser extent, comparison to no iron treatment; few such studies exist in NDD-CKD. In contrast, among patients receiving hemodialysis, three randomized clinical trials found no demonstrable efficacy for oral iron.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing oral to IV iron in this population have generally found greater efficacy for IV iron. 17,18 However, to truly understand oral iron efficacy, it would require parallel group testing against placebo or, to a lesser extent, comparison to no iron treatment; few such studies exist in NDD-CKD. In contrast, among patients receiving hemodialysis, three randomized clinical trials found no demonstrable efficacy for oral iron.…”
Section: Discussionmentioning
confidence: 99%
“…As with the other new formulations permitting a large (500-1,000 mg) dose in 15 min, iron isomaltoside has been shown to be safe and effective in chronic kidney disease, inflammatory bowel disease, chemotherapy induced anemia, and perioperatively [62][63][64][65].…”
Section: Administration Of Parenteral Iron In Practicementioning
confidence: 99%
“…Regarding sequence generation, 10 trials of patients with CKD stages 3 to 5 were of low risk of bias, 16,17,20,[22][23][24][25][26][27][28] whereas 3 were of unclear risk. 18,19,21 Seven trials of patients with CKD stage 5D were of low risk of sequence generation bias, 30-34,36,37 3 were of unclear risk, 29,35,38 and 1 was of high risk.…”
Section: Description Of Included Studiesmentioning
confidence: 99%